Performance indicator of tunnel linings under geotechnical uncertainty. Issue 2 (April 2016) - Spyridis, Panagiotis; Konstantis, Spyridon; Gakis, Angelos
Abstract: In the process of dimensioning a tunnel lining support an optimized structural system is pursued that can accommodate the inherent uncertainties associated with the geotechnical, hydro‐geological, and environmental conditions. Particularly for geotechnics, uncertainty has become a major issue of scientific discussion according to a number of recent publications. At the same time, advanced performance criteria often require probabilistic assessments in order to quantify a structure's safety and reliability or to inform life‐cycle engineering decisions. This contribution demonstrates a novel design approach for the design assessment of concrete tunnel linings. The Index for the Capacity Utilization of Linings in Tunnels (CULT‐I) introduced herein, facilitates the quantification of reliability of a tunnel lining support, while it aids toward a rationalized, performance‐based design optimization with considerations on geotechnical uncertainty. A typical case of a shallow urban tunnel excavated in soft ground using the TBM method is presented, demonstrating the practical application and feasibility of the proposed approach.